Employing Actual Shop-floor Status and Machine Tool Kinematic Data Model in Machining Simulation - Abdul Kadir, Aini Zuhra; Xu, Xun; Ridwan, Firman (International Journal of Integrated Engineering, 2011)
In machining simulation, there is always a trade-off between high level of accuracy, and an abstraction of reliance and truthful simulation environment. Most research work has been devoted towards developing precise models and algorithms, yet still lack the capability to portray the true machining environment. This is due to the difficulty in providing a simulation model of data integrity without continually monitoring the shop-floor activities. This factor is compounded by the use of low language data at shop-floor level that hinders the possibility for design data integration. It must be noted that, shop-floor activities are dynamic in nature. Even just prior to machining, machining parameters, cutting tools, workpiece and fixture orientations were adjusted where most of these activities are not being captured and considered in the simulation model. This paper introduces a near-real solution to cater for an ingenuous machining simulation environment. The approach taken is by employing machine tool kinematic data model based on STEP/STEP-NC and actual shop-floor status via MTConnect.